Pelatihan Pembuatan Preparat Segar dan Awetan Jamur serta Cara Mengidentifikasi Jamur Mikroskopik bagi Guru Biologi Sekolah Menengah Atas - Swandi, Monica Kharisma; Salmi, Salmi (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2025)
Fresh and preserve slide-culture preparation and identification of microscopic fungi workshop for biology teachers in senior high school was conducted as the community service activity. The aim of this workshop was to improve teachers's competency by providing a short lecture and training on fresh and preserve slide-culture preparation and identification of microscopic fungi. This workshop was held online using zoom meeting application and divided into four session; short lecture, group activity for identification of fungi, discussion and evaluation. The participant's knowledge about the topic evaluated two times, before the short lecture and after the discussion session using Google-form. Statistical analysis used paired sample t-test shown that the teachers's knowledge and skill in identification of microscopic fungi significantly improved after the workshop (p<0.05). As the workshop ended, the participant also got a tutorial video, pocketbook and preserved microscopic fungi slide-cluture. We hope the biology teachers can implement all they got during the workshop in learning process at school, so the students can understand the fungi topic better.